The Impact of New Technologies “E-Learning” on the Productivity of Companies in a Period of Crisis: Interviewing BPOs During Covid-19 - El Alji, Yasmine (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
New information and communication technologies have changed our economic and business functions. In this case, the training strategy has changed, disrupting the internal functioning of the organization. For this reason, information and communication technologies (ICT) must be applied in training, creating a new reality called “E-learning”. Indeed, the Covid-19 crisis has disrupted the economic system in all sectors and proved the limits of face-to-face training. As a result, the company is forced to change its habits and adapt more quickly to these turbulences to weather the financial crisis and ensure performance. This article aims to explore the contribution of e-learning to the commercial performance of three companies in the field of outsourcing and transaction management BPO’s in times of covid-19 crisis. A qualitative analysis was conducted: A series of semi-directional interviews were conducted with about 14 participants from the Human Resources Department. The companies studied have therefore embarked on this new practice, which is beginning to grow.